FOREIGN LANGUAGE CLASSROOM ANXIETY: AN INTERNATIONAL STUDENT’S PERSPECTIVE ON INDONESIAN LANGUAGE LEARNING - Mena, Ukhtie Nantika; Nurihsan, Ahmad Juntika; Ilfiandra, . (PUPIL: International Journal of Teaching, Education and Learning, 2020)
This study aims to explore the perspective on Foreign Language Classroom Anxiety (FLCA) of an International student. A descriptive narrative is used to discover written and spoken responses from the student. An online survey was employed as secondary data to identify the level of FLCA among six UPI international students. A student with the highest score volunteered to be interviewed. Several symptoms were found; lack of concentration, excessive worry, fear, unwanted thoughts, and sweating. The results showed that difficulties to understand lecturers’ correction, presentation, and fear of getting left behind are three major causes of his anxiety. For further research, the interactions between international students and materials, lecturers, and peers will be valuable findings in the scope of the study.